Water Supply Treatment Sustainability of Semambu Water Supply Treatment Process - Water Footprint Approach - Aziz E.A.; Malek M.A.; Moni S.N.; Hadi I.H.; Zulkifli N.F. (Institute of Physics Publishing, 2023)
Land use; Sustainable development; Water supply; Fresh water resources; Rainfall intensity; River water; Treatment process; Water consumption; Water demand; Water footprint; Water scarcity; Water treatment